Influence of Classroom Management Style on Senior Secondary Students’ Performance in Jos North Local Government Area - Shittu Lukman Olayinka; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2025)
This study examined the influence of Classroom management style on senior secondary students’ performance in Jos North Local Government Area. The study was guided by four objectives. Inline with these objectives the study answered four corresponding research questions and tested two null hypotheses. Extensive literature was reviewed. The research design employed was a survey research design specifically cross-sectional survey research design. The population of this study comprised 1,231 Senior Secondary School (SS II) students in the 22 registered public secondary schools in Jos North Local Government Area of Plateau State, Nigeria. From this population, a sample of 200 SS II students was selected from ten public secondary schools out of the 22 registered public using simple random sampling technique. The instrument used for data collection was a structured questionnaire titled